Taxonomy and ecology of mangrove fungi on selected hosts in Taklong Island, Guimaras - Biboso, Jesus Alexander N.
For the taxonomy of all fungi on three hosts, the ascomycetes are represented by 11 Orders, 25 Families, and 43 Genera. Order Dothideales is the most represented Order with 10 Families and 13 Genera. For the basidiomycete, it is represented only 1 Order, 1 Family, and 1 Genus, namely, Melanogastrales, Niaceae, Nia respectively. For Mitosporic Fungi, they represented by 29 genera. (p)Primarily the mycota examined are of tropical and marine origin and are associated with woody substrate. The salinity and temperature from August 1997 to July 1998 are at 28-32 0 , A. corniculatum - Kallichroma glabrum (34 C. inerne - Savoryella lignicola (57 and Sporidesmium sp. (32 collected varied on the three hosts: A. ilicifolius - Papuslapora sp. (57 The present study was conducted to investigate fungi colonizing a woody mangrove species Aegiceras corniculatum and two (2) mangrove associates-Acanthus ilicifolius and Clerodendrum inerme. Specifically, this study aims to 1) describe, identify and classify fungi collected on the mentioned hosts and 2) to determine the abundance and frequency of occurence of fungi collected from these hosts. Results of the study show that Clerodendrum inerne had the highest number of species collected (8); followed by A. corniculatum (68); and A. ilicifolius with only (45) species. This is the first record of fungal mycota reported for C. inerne. There was a relatively high percentage of ascomycetes collected on the three hosts compared with the mitosphoric fungi and basidiomycetes. These result imply that the ascomycetes were favored by a rleatively more lignocellulosic substrata (A.corniculatum >> C. inerne > A. ilicifolius). (p)The very frequent species (frequency of occurence > 30 and 22-32rcedilC, respectively. The very frequent fungi, namely: Papulaspora sp., Savoryella lignicola, Sporidesmium sp., and Kallichroma glabrum are directly influenced by salinity.